Fuzzy Order Convergence of Double Sequences in Fuzzy Riesz Spaces (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
In this paper, we introduce the concepts of fuzzy order convergence of double sequence, also define a new type of convergence, that is,  Convergence and  Cauchy of double sequence in fuzzy Riesz space and then prove some interesting results related to these notions.